PENGARUH BONUS DEMOGRAFI PADA PARTISIPASI PEMILU 2024 TERHADAP LITERASI POLITIK DIGITAL MAHASISWA ILMU PERPUSTAKAAN DAN INFORMASI ISLAM UIN SAYYID ALI RAHMATULLAH TULUNGAGUNG - Aulia Irfana, Sifa; Prajawinant, Arin (Jurnal Perpustakaan dan Informasi, 2024)
Presidential election and demographic bonus are two words that are closely related today. The presidential election which will take place on February 14 2024 will elect the president for the 2024-2029 term. Meanwhile, according to several organizations such as BPS and Bappenas, the demographic bonus will reach its peak in 2030 and end in 2040. At the population level ahead of the election, there will be demographic changes marked by an increase in the number of young voters (Generation Z and millennials) who are older. between 17 to 39 years. CSIS estimates that the number of young voters in the next election will reach 60% of the total electorate. The 2024 presidential election could be said to be the driving force or last opportunity for the Indonesian nation before entering the peak of its demographic opportunities. Approaching the 2024 election, especially during the campaign period, the spread of fake news (hoaxes) and misinformation is expected to increase. This can lead to increased polarization of society due to the unhealthy and irresponsible actions of several political interests. Implementing a good digital political culture is important for the current and future conditions of Indonesian society and young generations.